(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2023)
Thin-film nanocomposite (TFN) reverse osmosis (RO) membranes offer immense potential for revolutionizing water purification and desalination but face limitations including fouling, scaling, and high energy consumption. To address these challenges, researchers have explored incorporating various additives into TFN membranes. This review highlights the efficacy of organic and inorganic additives in overcoming these limitations and enhancing membrane performance by various additives, both organic and inorganic, into thin-film nanocomposite (TFN) reverse osmosis (RO) membranes has shown promise in overcoming the restrictions of possible nanoparticle leaching and improving membrane performance. In particular, the use of metal-organic frameworks (MOFs) has demonstrated significant potential. MOFs, such as ZIF-8, UiO-66, and MIL-101, have been successfully incorporated into TFN membranes, resulting in improved water flux, salt rejection, and antifouling characteristics. The unique features of MOFs, including high water permeability, broad surface area, and water stability, make them suitable for membrane modification. Additionally, the employment of zeolites, such as NaY and NaA, has been shown to enhance the permeate flux of TFN RO membranes without compromising salt rejection. Furthermore, the incorporation of non-organic additives, such as silica nanoparticles and halloysite nanotubes (HNTs), has demonstrated the potential to improve the thermal stability, permeate flux, and antifouling properties of TFN membranes. For instance, the inclusion of HNTs in the TFN membrane resulted in a greater flux compared to the pristine Thin Film Composite (TFC) membrane while maintaining a comparable salt rejection rate. Similarly, the integration of silica nanoparticles into TFN RO membranes has shown promise in improving their thermal stability, permeate flux, and salt rejection. However, careful control of nanoparticle concentration and dispersion is necessary to avoid agglomeration and maintain optimal membrane performance. Therefore, the incorporation of these additives into TFN RO membranes holds great potential for enhancing their performance and overcoming key challenges in membrane technology. Further research and development in this area are essential to unlock the full potential of these advanced membrane materials. Keywords: Desalination, Reverse osmosis membrane, SWCNT; MWCNT, Quantum Dots, Metallic additives, Nano composites